Pendidikan Islam menurut KH. Hasyim Asy’ari - Khoir, Mulyanto Abdul; Pramono, Agus; Yulianto, Rahmat; Rahman, Abdul; Sofiandi, M. (TSAQOFAH, 2026)
Islamic education is oriented not only towards the acquisition of knowledge but also towards the formation of the whole person through the integration of knowledge, adab, and akhlak, making the study of classical–modern thinkers and the relevance of their ideas to the national education curriculum crucial for addressing contemporary educational challenges. This study aimed to discuss the concept of Islamic education according to KH. Hasyim Asy’ari and analyse its relevance to the Kurikulum Pendidikan Nasional (National Education Curriculum) in Indonesia. A qualitative approach was employed using a literature study method of the works of KH. Hasyim Asy’ari, particularly Adab al-‘Ālim wa al-Muta‘allim, as well as various other relevant sources that examine educational thought and Islamic values. The findings show that KH. Hasyim Asy’ari views education as a process sof forming individuals who are faithful, pious, and possess noble character through the principles of prioritising adab before knowledge, sincerity in seeking and teaching knowledge, teacher exemplarity, and the integration of knowledge and practice. This concept of Islamic education is strongly aligned with the aims and direction of the National Education Curriculum, particularly in strengthening character education, developing teacher professionalism, mainstreaming religious moderation, and fostering students in a holistic manner. The study concludes that integrating KH. Hasyim Asy’ari’s Islamic educational values into the national education system is a strategic step to address modern educational challenges, especially in building students’ character, morality, and spirituality in a sustainable way.